ANALISIS MIMO UNTUK PENINGKATAN KAPASITAS SISTEM SELULER 4G LTE PADA SISTEM KOMUNIKASI HIGH ALTITUDE PLATFORM STATION - Waluyo, Catur Budi (Sekolah Tinggi Teknologi Adisutjipto, 2016)
The development of technology has opened up a new wireless infrastructure to complement the satellite and terrestrial networks. High Altitude Platforms (HAPs) is a communications infrastructure that uses air balloon as a solution between terrestrial and satellite communications systems with medium coverage and low cost o f launching and maintenance. HAPs can be joined with a Long Term Evolution (LTE) technology standardized by the Third Generation Partnership Project (3GPP). LTE uses orthogonal frequency division multiplexing (OFDM) technology for downlink. OFDM technology is a technology that uses multicarrier and bring the data in parallel and the bandwidth is divided into several subcarrier. To improve the performance of LTE in an increase in capacity, coverage, and speed of data, then it can use MIMO techniques. MIMO is a technique using multiple antenna transmitter and receiver antennas that are used to overcome the problem of multipath fading and increase the capacity of the system to be serviced. MIMO support the achievement of high transmission speed. In the simulation, signals generated by the modified jakes model into a ricean channel using the K factor 1.41, 1.99, 2.33, 2.66, 4.61, 6.35, 9.21, 12.15, 16.77 dB with elevation angle of 1 0 Â° to 90Â°. The larger the K factor, the smaller the shift doppler at each speed. Elevation angle have a relationship to the coverage area of HAPs, the smaller the elevation angle of the wider the coverage area, and the higher the position, the wider HAPs coverage area too. In ergodic capacity, the smaller the K factor, the smaller the elevation angle so that the capacity is also greater. System without estimation for the K factor o f 1.41dB and K 9.21dB is necessary for channel estimation and the Bit Error Rate (BER) o f the same system that made channel estimation has a better performance compared with the existing channel without estimation with the SNR improvement o f about 18 dB.